Oral self-care among adults with diabetes in Finland - Karikoski A, Ilanne-Parikka P, Murtomaa H (Blackwell Synergy, 2002)
The importance of maintenance and promotion of periodontal health is emphasized among people with diabetes because of their high risk for periodontal diseases.